2015
DOI: 10.1002/asi.23340
|View full text |Cite
|
Sign up to set email alerts
|

How online social interactions influence customer information contribution behavior in online social shopping communities: A social learning theory perspective

Abstract: Online social shopping communities are transforming the way customers communicate and exchange product information with others. To date, the issue of customer participation in online social shopping communities has become an important but underexplored research area in the academic literature. In this study, we examined how online social interactions affect customer information contribution behavior. We also explored the moderating role of customer reputation in the relationship between observational learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(67 citation statements)
references
References 62 publications
(73 reference statements)
1
57
0
1
Order By: Relevance
“…Findings from qualitative data provide evidence that consumers' social interactions (i.e., seek information about products and services from other consumers via diverse social media channels) positively influence their apparel purchasing online, therefore aligning with previous research (Angela & Neil, 2017;Cheung et al, 2015;Cui et al, 2012;Kulmala, 2011;Wang et al, 2012). In specific, findings from qualitative data demonstrated how social learning through information searches, online reviews, social interactions with trusted individuals, and/or channels alleviate risks consumers perceive during apparel purchasing online.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Findings from qualitative data provide evidence that consumers' social interactions (i.e., seek information about products and services from other consumers via diverse social media channels) positively influence their apparel purchasing online, therefore aligning with previous research (Angela & Neil, 2017;Cheung et al, 2015;Cui et al, 2012;Kulmala, 2011;Wang et al, 2012). In specific, findings from qualitative data demonstrated how social learning through information searches, online reviews, social interactions with trusted individuals, and/or channels alleviate risks consumers perceive during apparel purchasing online.…”
Section: Discussionsupporting
confidence: 81%
“…For example, according to Cheung, Liu, and Lee (2015), observing peer members' postings and reinforcement through peer members' recommendations in online apparel social shopping communities facilitates consumers' communication about apparel products. Also, Wang et al (2012) discussed reinforcement learning and how consumers communicate with peers about products via social media (i.e., talking about products, buying products, product information) and how they influenced each others' attitudes towards products.…”
Section: Literature Review 1 Theoretical Framework: Social Learnmentioning
confidence: 99%
“…Social learning theory provides a theoretical framework of how social interaction among members is related to meaningful learning occurred to the individual members. It is suggested that good interaction among members in a social environment is vital for the process of knowledge acquisition and learning to occur through active participation in that community (Cheung et al 2015). Another study by Zheng and Warschauer (2015) confirms that when students have strong interaction in their social environment they tend to gain good academic performance.…”
Section: Social Interactionmentioning
confidence: 97%
“…In such community, meaningful learning and information attainment are achieved by social interaction when members have willingness to exchange information, provoke inspiring questions and suggest fruitful opinions to grow their individual intellectuality (eg, Cheung et al 2015). Interaction among peers is important in enhancing learning among community members (Oh et al 2014).…”
Section: Social Interactionmentioning
confidence: 99%
“…For this project, we focused on experience products, because these goods are naturally the focus of collaborative search and collaborative retail shopping tasks, where information sharing occurs during the shopping activity [15]. Although there are other possible contexts for experience goods, such as online reviews or social media platforms, it also seems natural for collaborative searching where individual can share their opinions and insights.…”
Section: System Developmentmentioning
confidence: 99%